2011
DOI: 10.1164/rccm.201012-2010oc
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Lung Elastase Activity Enables Lung Growth in Mechanically Ventilated Newborn Mice

Abstract: Rationale: Mechanical ventilation with O 2 -rich gas (MV-O 2 ) offers life-saving treatment for respiratory failure, but also promotes lung injury. We previously reported that MV-O 2 of newborn mice increased lung elastase activity, causing elastin degradation and redistribution of elastic fibers from septal tips to alveolar walls. These changes were associated with transforming growth factor (TGF)-b activation and increased apoptosis leading to defective alveolarization and lung growth arrest, as seen in neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
72
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 63 publications
6
72
0
1
Order By: Relevance
“…We wondered if this might reflect a difference in lung elastase activity that has been linked to MV of newborn mice (10,11). We indeed found that MV increased serine elastase activity in the lungs of Eln ϩ/ϩ mice but not in the Eln…”
Section: Discussionmentioning
confidence: 90%
“…We wondered if this might reflect a difference in lung elastase activity that has been linked to MV of newborn mice (10,11). We indeed found that MV increased serine elastase activity in the lungs of Eln ϩ/ϩ mice but not in the Eln…”
Section: Discussionmentioning
confidence: 90%
“…Our results confirm recently published experiments showing that prolonged ventilation with 40% oxygen increased MMP9 and elastase activity, resulting in elastin degradation and emphysematous alveoli, similar to findings in BPD. Treatment with the elastase inhibitor elafin showed promising reduction of these alterations (6,25). Similar to pediatric with acute respiratory distress syndrome (ARDS) patients, in which higher MMP9 and MMP8 activity in tracheal aspirates was correlated with a longer need for MV (26), an increase in MMP8 in bronchoalveolar lavage fluid and lung tissue of rodents was observed after exposure to high-pressure ventilation or prolonged (48 h) high oxygen exposure (27).…”
Section: Discussionmentioning
confidence: 92%
“…Models trying to decipher genes involved in the pathophysiology of BPD are mainly based on MV and oxygen application to young mammals with immature lungs of different species (3). In newborn rodent models, analyses of lung structure and gene and protein expression are performed for practical reasons directly at the end of MV (4)(5)(6). However, later appearing changes of gene expression might also have an impact on lung development and the evolution towards BPD and cannot be discovered by such models.…”
mentioning
confidence: 99%
“…Excessive elastase activity has been considered as a mediator of pathological elastin degradation, which might underlie the paucity of elastin and bizarre elastin fiber patterns seen in affected lungs (21)(22)(23)36). Additionally, the altered expression of proteins required for proper elastin fiber assembly has also been suggested to uncouple elastin synthesis and the assembly of elastin fibers (7)(8)(9).…”
mentioning
confidence: 99%